ANALISIS ANALISIS KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH MELAKUKAN AKUISISI PADA PERUSAHAAN PENGAKUISISI (STUDI KASUS PERUSAHAAN PUBLIK NON-KEUANGAN YANG MELAKUKAN AKUISISI PADA TAHUN 2019) - Putri, Devina Dianra; Yunita, Irni (LPPM STIE Muhammadiah Bandung, 2023)
The era of economic globalization in Indonesia not only has a positive impact but also has a negative impact in increased competition between industries. This challenge can be solved by restructuring the company with an external expansion strategy, such as acquisitions. Acquisition activity increased and developed in 2019. Acquisitions does not always have a positive impact on the company's financial performance. The purpose of this research is descriptive comparative by analyzing financial performance using financial ratios before and after the acquisition. The method used is quantitative and the Wilcoxon Signed Rank Test as a comparison in the two years before and after the acquisition. The sampling technique used was purposive sampling of 8 companies. The results of this study indicate that there is a significant difference in the debt to asset ratio while the current ratio, debt to equity ratio, total asset turnover, return on assets and return on equity do not show a significant difference.